Prediksi Trend Harga Saham Jangka Pendek berdasarkan Fitur Technical Analysis dengan menggunakan Algoritma Random Forest - Michael Eggi Bastian; Bayu Rahayudi; Dian Eka Ratnawati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Stock trading is a daily activity carried out by a stock trader. A stock trader can perform this trading activity on a capital market. In the capital market, you can see a chart that depicts the price movement of a stock in a certain period, also known as